Description of Ascariasis in Children Aged 2 to 12 Years at the Martha Friska Hospital, Pulo Brayan, Medan - Said Munazar Rahmat (Buletin Farmatera, 2020)
Province of North Sumatera is one of the provinces with the most Ascariasis cases which affects children. This study aims to determine the description of ascariasis patients aged 2-12 years who are treated at the Martha Friska Pulo Brayan Hospital, Medan. This study is a descriptive study with a method cross-sectional, using consecutive sampling, which was conducted on patients who met the inclusion criteria from January to October 2017. The results of the study showed that most of the ascariasis subjects were male, pre-school age with good nutritional status, had normal Hb and Eosinophil levels.